A systematic review of the effect of emergency medical service practitioners’ experience and exposure to out-of-hospital cardiac arrest on patient survival and procedural performance - Dyson, K.; Bray, J.; Smith, K.; Bernard, S.; Finn, Judith (Elsevier, 2014)
Background and objective: Emergency medical service (EMS) practitioners’ experience and exposure to out-of-hospital cardiac arrest (OHCA) and advanced life support (ALS) procedures could be an important factor in procedural success and patient survival. We systematically reviewed the literature to examine these associations. Methodology: We searched for publications using MEDLINE, EMBASE, CINAHL, CENTRAL and Web of Science. We included studies examining any type of EMS practitioner (e.g. paramedics, physicians) and OHCA patients of all ages and aetiologies. Two reviewers independently extracted data. Results: The search identified 1658 citations, of which 11 observational studies of variable quality were included. The majority of studies did not adjust for important confounding factors and reported across different EMS personnel structures. OHCA survival was not consistently associated with various definitions of career experience in three studies, or with previous OHCA exposure in another study. Endotracheal intubation (ETI) was the only ALS procedure examined. Successful ETI placement was associated with the previous number of ETIs performed in four of five studies, but not career experience in three of four studies. Only one study examined OHCA outcome, and reported an increase in survival to hospital discharge when practitioners had high ETI exposure. Conclusions: There is no clear evidence of an association with EMS practitioner career experience or exposure to OHCA cases and ALS procedures, with the exception of exposure to ETI and successful placement. However, most studies in this field had substantial risk of bias. Therefore, further studies are required before any definitive conclusions can be drawn.